If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3q = 11q Solving 3q = 11q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-11q' to each side of the equation. 3q + -11q = 11q + -11q Combine like terms: 3q + -11q = -8q -8q = 11q + -11q Combine like terms: 11q + -11q = 0 -8q = 0 Divide each side by '-8'. q = 0 Simplifying q = 0
| 18x^2+25x-15=0 | | 4(2x-6)=3c | | 73*10+6+-13=723 | | 73*10+6-13=723 | | 4c+4d+2c-8d= | | z+2iz=2i+1 | | 9x-100=3x-10 | | -3-4x=5-6x | | 36/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4=0 | | 3x+9=31-5x | | 36/0.4=1231 | | 36/0.4=0 | | -1-4x=5-6x | | 16-4[9-3(2x-5)]=-4(3-6x) | | 7x*12y=2a*12b | | 3-4x=5-6x | | x+12=13-x | | 2x+12=6-4x | | x-4=2x-17+9 | | 4sinx=-cos^2x+4 | | 45y=15 | | 12*(x^17)=60 | | 1-5[7+2(3x-1)]=-6(4+5x) | | 1111=100 | | 42-9y=33 | | 5-kx=2k-x^2 | | x^2-kx-2k+5=0 | | m=2/3(-5,5) | | 5n+67=8n-11 | | X-2X/100=600 | | 5+2x=x+13 | | (x4y2_3x3y-5xy_6)$(x2y_2xy-2)/ |